Intermittent Hypoxia-Induced Activation of Endothelial Cells Is Mediated via Sympathetic Activation-Dependent Catecholamine Release - Cetin-Atalay, Rengul; Meliton, Angelo Y.; Wu, David; Woods, Parker S.; Sun, Kaitlyn A.; Peng, Ying-Jie; Nanduri, Jayasri; Su, Xiaoyu; Fang, Yun; Hamanaka, Robert B.; Prabhakar, Nanduri; Mutlu, Gökhan M. (Frontiers in Physiology, 2021)
Obstructive sleep apnea (OSA) is a common breathing disorder affecting a significant percentage of the adult population. OSA is an independent risk factor for cardiovascular disease (CVD); however, the underlying mechanisms are not completely understood. Since the severity of hypoxia correlates with some of the cardiovascular effects, intermittent hypoxia (IH) is thought to be one of the mechanisms by which OSA may cause CVD. Here, we investigated the effect of IH on endothelial cell (EC) activation, characterized by the expression of inflammatory genes, that is known to play an important role in the pathogenesis of CVD. Exposure of C57BL/6 mice to IH led to aortic EC activation, while in vitro exposure of ECs to IH failed to do so, suggesting that IH does not induce EC activation directly, but indirectly. One of the consequences of IH is activation of the sympathetic nervous system and catecholamine release. We found that exposure of mice to IH caused elevation of circulating levels of catecholamines. Inhibition of the IH-induced increase in catecholamines by pharmacologic inhibition or by adrenalectomy or carotid body ablation prevented the IH-induced EC activation in mice. Supporting a key role for catecholamines, epinephrine alone was sufficient to cause EC activation in vivo and in vitro. Together, these results suggested that IH does not directly induce EC activation, but does so indirectly via release of catecholamines. These results suggest that targeting IH-induced sympathetic nerve activity and catecholamine release may be a potential therapeutic target to attenuate the CV effects of OSA.